2015
DOI: 10.1007/s13277-015-3380-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pathological characteristics of breast cancer patients with secondary diabetes after systemic therapy: a retrospective multicenter study

Abstract: The objective of this study was to investigate the clinical pathological characteristics of breast cancer (BC) patients with secondary diabetes after systemic therapy without preexisting diabetes. A total of 1434 BC patients received systemic therapy and were analyzed retrospectively. Fasting plasma glucose (FPG) levels were monitored prior to the treatments, during the course of systemic therapy, and at the follow-up visits. Cox regression models were used to estimate the associations between the clinical pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The risk of diabetes may be mediated by common shared risk factors such as old age, obesity, 6 insulin resistance, 7 sedentary lifestyle, and diet, 8 and emerging evidence, although limited by its infancy, points to breast cancer adjuvant treatment as potentially leading to the development of diabetes. 9- 13 The precise biologic mechanism remains unclear. Weight gain 10 and hyperglycemia 11 have been proposed in the chemotherapy setting, whereas dysregulations in insulin secretion associated with estrogen depletion and subsequent alterations in glucose homeostasis 9,12 have been suggested as plausible pathways in the hormone therapy (HT) setting.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of diabetes may be mediated by common shared risk factors such as old age, obesity, 6 insulin resistance, 7 sedentary lifestyle, and diet, 8 and emerging evidence, although limited by its infancy, points to breast cancer adjuvant treatment as potentially leading to the development of diabetes. 9- 13 The precise biologic mechanism remains unclear. Weight gain 10 and hyperglycemia 11 have been proposed in the chemotherapy setting, whereas dysregulations in insulin secretion associated with estrogen depletion and subsequent alterations in glucose homeostasis 9,12 have been suggested as plausible pathways in the hormone therapy (HT) setting.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 From a clinical perspective, although different in the pathogenesis and disease progression, both ailments share the etiology and signaling pathways 23 and aspects such as old age, obesity, genetic predisposition, sedentary lifestyle, and chronic inflammation have a forbearing on the development of these ailments. 14 In addition, to these reports also suggest that females afflicted with breast cancer have an increased risk of developing diabetes and that this can have an adverse effect on their general health and quality of life. Incidence of Secondary Diabetes in Women who have Undergone Curative Chemotherapy for Breast Cancer Rao et al…”
Section: Discussionmentioning
confidence: 99%
“…7 Administration of steroid to mitigate emesis and inflammatory reactions is shown to induce steroid-induced hyperglycemia and diabetes in people undergoing therapy for cancer. [8][9][10][11][12][13][14][15] Previous studies have shown that almost 20% of nondiabetic cancer patients develop steroid-induced diabetes after antiemetic dexamethasone therapy. 5 Although not clear, these negative effects of steroids are attributed to myriad factors, the most important being increased insulin resistance and glucose intolerance, reduced β-cell mass from β-cell dysfunction, and increased hepatic insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Although the b-cell population can be regenerated in adults following injury (Bonner-Weir et al, 2010), the rate of replication is extremely low (Butler et al, 2003;Meier et al, 2008;Tyrberg et al, 2001), and the capacity for replication driven by replicative aging may play an important role in humans (Yanagiya et al, 1993), limiting the potential for replacement of damaged b-cells. However, studies aimed to evaluate diabetic potential of individual chemotherapeutics are lacking (Juanjuan et al, 2015). Interestingly, we found that although INS-1 832/13 cells responded to doxorubicin treatment with robust increased expression of both NQO1 and HO-1, genes involved in antioxidant response, this pathway was significantly less induced in native islets of Langerhans (Figure 4B and D).…”
Section: Capacity Of Doxorubicin To Contribute To the Onset Of Diabetesmentioning
confidence: 92%